Pengukuran Kesiapan Pembelajaran Daring di Tengah Pandemi COVID-19: Studi Kasus Universitas Budi Luhur: Measurement of E-Learning Readiness during the COVID-19 Pandemic: A Case Study of Universitas Budi Luhur - Titin Fatimah (DRPM Universitas Budi Luhur, 2021)
The world is currently experiencing a big issue since the World Health Organization (WHO) announced the global pandemic status of Corona Virus Disease 2019 (COVID-19). To prevent the spread of COVID-19, university leaders must choose to disable lecture activities in the campus environment and enforce online learning for students. E-learning is one type of learning that utilizes information and communication technology then it can be accessed by students anytime and anywhere. Universitas Budi Luhur has implemented e-learning since 2019, but there is still unpreparedness in its implementation. It is necessary to measure quantitatively to determine the level of e-learning readiness of Universitas Budi Luhur. E-learning readiness level measured based on the e-learning readiness model used. Data collection uses questionnaires and interviews, while data processing uses descriptive statistical techniques. The results show that the Universitas Budi Luhur e-learning readiness index is at a ready level yet only needs improvement in implementing it. Keywords : e-learning, model, readiness